Optimasi Konsentrasi Primer Dan Suhu Annealing Dalam Mendeteksi Gen Blaz Pada Bakteri Methicillin Resistant Staphylococcus Aureus Di Udara: Optimization of Primary Concentration and Annealing Temperature in Detecting Blaz Gene in Airborne Methicillin-resistant Staphylococcus aureus Bacteria - Mardiana, Anisah; Dhanti, Kurnia Ritma; Kurniawan, Kurniawan; Sulistyowati, Retno (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Staphylococcus aureus is a species of bacteria that is often identified as a source of infection and has increased the number of cases of resistance. Resistance to Penicillin-class antibiotics in S. aureus is associated with plasmids containing the blah-Z gene encoding ß-Lactamase. Some factors that can be modified to obtain optimal test results in PCR are annealing temperature and primary concentration. This study aims to identify the primary concentration and annealing temperature that produce PCR products with the best band in detecting the blaZ gene in Metichilin Resistant Staphylococcus aureus (MRSA) bacteria. The research design used used experimental methods. The results of the study obtained were PCR products at primary concentrations of 10 μM were clearly visible, thick and clean, compared to primary concentrations of 5 μM. Annealing temperature with the best band results at temperatures of 61.8 °C and 58.7°C. This study concluded the primary concentration to obtain a clearly visible band result of 10 μM. The annealing temperature of 61.8°C produced the best band in the sample code R.PG. U4, R.V.U2, and R.151.U2 temperatures. While the sample code R.IGD. U5 band results best at annealing temperature 58.7°C.